Interaction of silicon and manganese in nutritional and physiological aspects of energy cane with high fiber content - Oliveira, Kamilla Silva [UNESP]; de Mello Prado, Renato [UNESP]; Checchio, Mirela Vantini [UNESP]; Gratão, Priscila Lupino [UNESP] (Springer Nature, 2022)
Background: Silicon (Si) is a multiple stress attenuator element in plants, however more research is needed to elucidate the actions in the plants defense system with low nutrition of manganese (Mn) for a prolonged period, and the attenuation mechanisms involved in the effects of Mn deficiency on energy cane with high fiber content. Thus, the objective of this study was to evaluate whether Si reduces the oxidative stress of the energy cane grown in low Mn in nutrient solution, to mitigate the effects of Mn deficiency, improving enzymatic and non-enzymatic defense, uptake of Mn the plant growth. Methods: An experiment was carried out with pre-sprouted seedlings of Saccharum spontaneum L. in a 2 × 2 factorial scheme in five replications in which the plants were grown under sufficiency (20.5 μmol L−1) and deficiency (0.1 μmol L−1) of Mn combined with the absence and presence of Si (2.0 mmol L−1) for 160 days from the application of the treatments. The following parameters were evaluated: accumulation of Mn and Si, H2O2, MDA, activity of SOD and GPOX, total phenol content, pigments, and quantum efficiency of PSII. Results: Mn deficiency induced the oxidative stress for increase the H2O2 and MDA content in leaves of plants and reduce the activity of antioxidant enzymes and total phenols causing damage to quantum efficiency of photosystem II and pigment content. Si attenuated the effects of Mn deficiency even for a longer period of stress by reducing H2O2 (18%) and MDA (32%) content, and increased the Mn uptake efficiency (53%), SOD activity (23%), GPOX (76%), phenol contents, thus improving growth. Conclusions: The supply of Si promoted great nutritional and physiological improvements in energy cane with high fiber content in Mn deficiency. The results of this study propose the supply of Si via fertirrigation as a new sustainable strategy for energy cane cultivation in low Mn environments.
Keywords: Abiotic stress; Guaiacol peroxidase; Hydrogen peroxide; Oxidative stress; Phenols; Superoxide dismutase; Uptake efficiency